Holistic Analysis of Triple Bottom Line on Performance and Sustainability of the Hospitality Industry in Kendari City (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Triple Bottom Line (TBL), a concept developed by John Elkington in 1994, emphasizes three main aspects in measuring corporate performance: profit, people, and planet. This study highlights the specific challenges in implementing TBL in the hospitality industry in Kendari, which tends to overlook social and environmental aspects. This knowledge gap is addressed by exploring the application of TBL in Kendari hotels through a case study approach combining qualitative and quantitative data analysis. The main findings show that the implementation of TBL in Kendari hotels significantly enhances economic, social, and environmental performance. Hotels adopting TBL experience improved operational efficiency, employee and customer satisfaction, and reduced carbon emissions and waste. Challenges in implementation, such as resource and knowledge limitations, are identified but can be overcome with support from the government and local communities. The study's implications suggest that TBL implementation can be an effective strategy for achieving long-term sustainability in the hospitality industry, particularly in small cities like Kendari. This study significantly contributes to the theory and practice of human resource management and sustainability by offering practical recommendations to improve hotel performance and sustainability. Despite limitations in data scope and methodology, these findings provide a strong foundation for further research.